INTERPRETASI STRUKTUR KERAK DAN MANTEL ATAS DI BAWAH PROVINSI BENGKULU MENGGUNAKAN TOMOGRAFI SEISMIK WAKTU TUNDA - , Ade Stepani Sudiyant ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bengkulu is one of Province in the southern of Sumatra which is its geological structure influenced by increasing of tectonic activities. It is noted by active earthquake due to fault and volcanoes activities and also subduction zone existance along west coast. Seismic Tomography method is used to delineatethe subsurface stucture. Using LOTOS-12 program and data inputfrom seismic wave. The interpretation of subsurface based on the P-wave and S- wave velocity variation is got to resulted negative velocity anomaly from Bukit Barisan Mountain. The lowest negative anomaly is beneath volcanoes with the deviation velocity is-5 % (Vp = 7.35 km/s dan Vs = 4.19 km/s) and it is found partial melting existance in 110-130 km depth. The negative anomaly with low velocity is estimated as fluids and subduction slub melting. From inversion processing is got velocity increasing from 25 to 35 km depth which is estimated as transition zona from crust to upper mantle noted by mohorovisic discontinuitiy.